REFOCUS-PULSAR Recovery-Oriented Practice Training in Adult Primary Mental Health Care: Exploratory Findings Including From a Pretest–Posttest Evaluation - Enticott, Joanne C.; Shawyer, Frances; Brophy, Lisa Mary; Russell, Grant; Mazza, Danielle; Wilson-Evered, Elisabeth; Weller, Penelope June; Slade, Mike; Edan, Vrinda; Meadows, Graham Nicholas (Frontiers in Psychiatry, 2021)
Objectives: Australian General Practitioners (GPs) are pivotal in mental health care. The REFOCUS-PULSAR (Principles Unite Local Services Assisting Recovery) primary care study aimed to improve personal recovery outcomes in adults with mental health problems consulting GPs. Design: Modified from an intended stepped-wedge cluster study, an exploratory (pre- and post-intervention) design employed cross-sectional surveys of patients consulting GPs. Setting: Eighteen primary care sites (clusters) in Victoria, Australia in 2013-2017. Participants: From 30 GPs recruited, 23 participated (76%), with 235 patient surveys returned from adults aged <75 years receiving mental health care. Intervention: A co-delivered face-to face training intervention for GPs in recovery-oriented practice (ROP), with personal recovery a key focus, used multimedia, mnemonics, and targeted interview schedules to encourage ROP - with availability of support sessions for one year. Outcome measures: Primary: the Questionnaire about the Process of Recovery full-scale score (outcome). Secondary: INSPIRE (experience), Warwick-Edinburgh Mental Well-being Scale (WEMWBS) and Kessler Psychological Distress Scale (K10) (outcomes). Other: General-practice-Users Perceived-need Inventory (experience). Results: Small positive significant effects indicated primary-outcome post-intervention improvements (t-test (233)=-2.23, p=0.01), also improvement in two secondary outcomes (WEMWBS t(233)= -2.12, p=0.02 and K10 t(233)= 2.44, p=0.01). More patients post-intervention reported ‘no need’ for further help from their GP; but in those reporting needs, there was greater unmet need for counselling. Conclusions: ROP implementation, internationally influential in specialist mental health care, here is explored in primary care where it has had less attention. These exploratory findings suggest better patient outcomes followed introducing GPs to ROP in routine practice conditions. Higher unmet need for counselling post-intervention reported by patients might be a sign of limited supply despite ROP facilitating better identification of needs. Challenges in project implementation means that these findings carry risks of bias and flag the importance establishing research infrastructure in primary care. Trial registration: ACTRN12614001312639